No link to cardiac valvulopathy was seen in cabergoline treated patients - K Dharshini; Noel Somasundaram; HMDPK Senevirathna; S Raj Kumar (Sri Lanka Journal of Diabetes Endocrinology and Metabolism, 2012)
Objective: To evaluate the association between use of cabergoline in patients with prolactinoma and risk of developing clinically relevant cardiac valvular disease. Method: This was a descriptive cross sectional study conducted at Endocrinology and Pituitary clinics at National Hospital of Sri Lanka. Patients with macro and micro prolactinoma who were on medical therapy with cabergoline for more than 24 weeks duration were selected for the study. Patients with pre existing congenital valvular heart disease, history of rheumatic heart disease and ischemic heart disease were excluded from the study. All the included patients were evaluated with 2D echocardiogram for the presence and degree of valvulopathy. Results: Out of 45 patients included in this study, 12 (26.6%) had mild valvular regurgitation. Twenty four patients received more than the median cumulative dose of 104 mg and the prevalence of valvulopathy was not significantly different (Chi-Squared test; p=0.34) from those receiving less than the median cumulative dose. Similarly 23 patients received treatment longer than the median duration of 48 months and the prevalence of valvulopathy was not significantly different (Chi-square test; p=0.92) from those received less than the median duration. Conclusion: Our study shows no significant association between the cumulative dose and the duration of cabergoline therapy with the development of valvulopathy among patients with prolactinoma. Sri Lanka Journal of Diabetes, Endocrinology and Metabolism 2012; 2: 69-72 DOI: http://dx.doi.org/10.4038/sjdem.v2i2.4775